Biochemical characterization of SARS-CoV-2 nucleocapsid protein - Zeng, Weihong; Liu, Guangfeng; Ma, Huan; Zhao, Dan; Yang, Yunru; Liu, Muziying; Mohammed, Ahmed; Zhao, Changcheng; Yang, Yun; Xie, Jiajia; Ding, Chengchao; Ma, Xiaoling; et al. (Biochemical and biophysical research communications, 2020)
The nucleocapsid (N) protein is an important antigen for coronavirus, which participate in RNA package and virus particle release. In this study, we expressed the N protein of SARS-CoV-2 and characterized its biochemical properties. Static light scattering, size exclusive chromatography, and small-angle X-ray scattering (SAXS) showed that the purified N protein is largely a dimer in solution. CD spectra showed that it has a high percentage of disordered region at room temperature while it was best structured at 55 °C, suggesting its structural dynamics. Fluorescence polarization assay showed it has non-specific nucleic acid binding capability, which raised a concern in using it as a diagnostic marker. Immunoblot assays confirmed the presence of IgA, IgM and IgG antibodies against N antigen in COVID-19 infection patients’ sera, proving the importance of this antigen in host immunity and diagnostics. •SARS-CoV-2 nucleocapsid protein is full of coils and highly disordered.•SARS-CoV-2 N protein forms a dimer by CTD-CTD interaction.•SARS-CoV-2 N protein can bind with non-specific nucleic acid with high affinity.•SARS-CoV-2 N protein can be a good antigen for serological test of COVID-19.